The Brazilian Registry of Juvenile Dermatomyositis (JDM): I- Onset Clinical Features and Disease Activity Scores by DAS-20 over 2-Years-Follow Up - Carneiro, Beatriz (2023)
Univ Sao Paulo, Inst Crianca, Sao Paulo, SP, Brazil